PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MATAHARI DEPARTMENT STORE .Tbk BRILYAN PLAZA KENDARI - Juliani, Lilis; Djauhar, Asri; Titop, Herman (Sultra Journal of Economic and Business, 2023)
This study aims to determine the effect of the work environment on employee performance at PT. Matahari Department Store tbk Brilyan Plaza Kendari. To achieve these objectivies, qualitative, and quantitative data are used, data collection techniques by observation, interviewes and literature study are used.Population in this study amounted to 65 people who are employees of PT. Matahari Department Store tbk Brilyan Plaza Kendari. Sampling using the Slovin formula. The data collection instrument used a questionnaire with a likert scale, each of wich had been tested and had met the validity and reliability requirements. Data analysis using simple linear regression and using hypothesis testing namely partial t test and determination R test. Based on the results of simple linear regression analysis shows that there is a positive influence between the work environment on employee performance at PT. Matahari Department Store tbk Brilyan Plaza Kendari with a tcount 12,001 > ttable 1,998 with a significance value of 0,000 < 0,05. So that the proposed hypothesis can be accepted. Based on this, it shows that the work environment has a positive effect on employee performance at PT. Matahari Department Store tbk Brilyan Plaza Kendari.